Implementasi Pendidikan Karakter Melalui Kegiatan Literasi Sekolah Dasar - Alya Maisya Putri; Adrias Adrias; Aissy Putri Zulkarnaini (Lembaga Pengembangan Kinerja Dosen, 2025)
This article aims to explore the implementation of character education through literacy activities in primary schools. This research uses a descriptive qualitative approach with a literature study method of a number of relevant previous studies. Data were collected through document analysis and scientific articles, especially those discussing the integration of literacy and character values in primary school settings. The results of the study show that the implementation of literacy activities, such as reading 15 minutes before lessons, managing reading corners in the classroom and involving teachers and parents in reading habituation, can instill character values such as discipline, responsibility, cooperation and love of reading. Literacy activities not only play a role in improving students' literacy skills but are also effective in building a school culture that supports holistic character strengthening.